2012
DOI: 10.1111/j.1440-1746.2011.07054.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of critical host factor, IL‐28B, associated with response to hepatitis C virus treatment

Abstract: Chronic hepatitis C affects 2.2-3.0% of the world population (130 million-170 million). Pegylated interferon-a (PEG-IFN-a) in combination with ribavirin (RBV), the approved and standard therapy, leads to viral eradication in about 50% of treated patients. In 2009, genome-wide association studies (GWAS) identified host genetic variation to be critical for predicting treatment response and spontaneous clearance in patients infected with hepatitis C virus (HCV). A correlated set of polymorphisms in the region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…Although sex and age have been reported as the factors that influence the outcome of HCV infection, in this study statistical analysis did not show any association between sex ( P = 0.6), age ( P = 0.47) and outcome of HCV infection .…”
Section: Discussioncontrasting
confidence: 80%
“…Although sex and age have been reported as the factors that influence the outcome of HCV infection, in this study statistical analysis did not show any association between sex ( P = 0.6), age ( P = 0.47) and outcome of HCV infection .…”
Section: Discussioncontrasting
confidence: 80%
“…The 3 and 5-year DFS was reported for EGC in three 8 10 and four 8 10 , 22 studies, respectively. The meta-analysis of the 3 and 5-year DFS of ER versus SR showed no statistically significant difference, with pooled RRs of 0.92 (95% CI 0.84–1.01, P = 0.07) and 0.95 (95% CI 0.86–1.05, P = 0.30), based on a random-effects model due to significant interstudy heterogeneity ( P = 0.004, I 2 = 82%; P < 0.0001, I 2 = 88%, respectively) (Figure 4 ).…”
Section: Resultsmentioning
confidence: 94%
“…It has also been reported that demographic factors such as gender and age could influence the outcome of therapy in patients with HCV infection (5, 42). Although in this study no association was found between gender and response to therapy, the frequency of females who did not respond to therapy was higher than responders (10% versus 20%).…”
Section: Discussionmentioning
confidence: 99%